Aspek Hukum Pemberian Subsidi oleh Negara di dalam Lalu Lintas Perdagangan Internasional (Lex Jurnalica, 2008)
Every we mull over international trade, so that appear in head that are export activity and import. This matter is then evokes question to us that is, why do export activity. Easyly answer because export to give to chance vast for job area, besides pass export activity all at once ilaku another activity, like currency transfer (exchange rate), transfer document (exchange document), involve insurence (insurance) activity, involve transportation of goods (transportation). To make easy us realize export activity and import, so necessary seen from aspect micro economy that is activity supply and demand that in market mechanism. Supply can like as activity export and demand as import activity. Pass number comprehension exports and import, all at once we realize surplus or deficit a international commercial activity in country. International trade very related to international agreement between two countries. International trade law explanation divisible into two parts. In international trade law vast explanation law that regulates between country with country in sketch relations of international law. While in trade law narrow explanation internasioanal agreement between country with country other so that effort executant (subjek law) with effort executant can do trade.Keywords: Country, Subsidy, Activity Eksport Import